Tunable Wood by Reversible Interlocking and Bioinspired Mechanical Gradients. Issue 10 (28th March 2019) - Frey, Marion; Biffi, Giulia; Adobes‐Vidal, Maria; Zirkelbach, Meri; Wang, Yaru; Tu, Kunkun; Hirt, Ann M.; Masania, Kunal; Burgert, Ingo; Keplinger, Tobias
Abstract: Elegant design principles in biological materials such as stiffness gradients or sophisticated interfaces provide ingenious solutions for an efficient improvement of their mechanical properties. When materials such as wood are directly used in high‐performance applications, it is not possible to entirely profit from these optimizations because stiffness alterations and fiber alignment of the natural material are not designed for the desired application. In this work, wood is turned into a versatile engineering material by incorporating mechanical gradients and by locally adapting the fiber alignment, using a shaping mechanism enabled by reversible interlocks between wood cells. Delignification of the renewable resource wood, a subsequent topographic stacking of the cellulosic scaffolds, and a final densification allow fabrication of desired 3D shapes with tunable fiber architecture. Additionally, prior functionalization of the cellulose scaffolds allows for obtaining tunable functionality combined with mechanical gradients. Locally controllable elastic moduli between 5 and 35 GPa are obtained, inspired by the ability of trees to tailor their macro‐ and micro‐structure. The versatility of this approach has significant relevance in the emerging field of high‐performance materials from renewable resources. Abstract : Wood is turned into a versatile engineering material by delignification, wet shaping, and spatial tuning of the mechanical and chemical properties. Biological design principles such as density gradients and fiber alignment are implemented to optimize for external loading conditions. A moisture‐triggered reversible interlocking between wood cells provides formability in the wet state and high strength and stiffness in the dry state.